2017
DOI: 10.5152/dir.2017.16617
|View full text |Cite
|
Sign up to set email alerts
|

High-pitch dual-source CT angiography without ECG-gating for imaging the whole aorta: intraindividual comparison with standard pitch single-source technique without ECG-gating

Abstract: C omputed tomography angiography (CTA) of the aorta is the reference method to investigate aortic disease and to follow up patients after surgical or endovascular aortic repair, either thoracic or abdominal. Thoracic aorta usually demands electrocardiography (ECG)-gated CTA to avoid motion artifacts related to cardiac cycle, notably for imaging aortic root and ascending segment (1). However, ECG-gating results in significantly increased radiation exposure, notably in case of low-pitch acquisition for retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
1
6
0
2
Order By: Relevance
“…In our study, it was observed that the patients had very low dose of radiation, such as 1.1 ± 0.2 mSv, on ash mode. This result was found to be consistent with previous studies (12,27,33). In order to use ash mode in dual-energy CT devices, patients' heart rates should be low (28,29).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, it was observed that the patients had very low dose of radiation, such as 1.1 ± 0.2 mSv, on ash mode. This result was found to be consistent with previous studies (12,27,33). In order to use ash mode in dual-energy CT devices, patients' heart rates should be low (28,29).…”
Section: Discussionsupporting
confidence: 92%
“…At the full-text level, 18 studies were excluded, and 26 were finally included in the review (Fig. 1) (1237). From these 26 studies (1237), 18 performed CNR measurements using only the thoracic aorta as the object of interest, six used only the pulmonary arteries, and two used both the thoracic aorta and pulmonary arteries.…”
Section: Resultsmentioning
confidence: 99%
“…These images can be obtained either with or without ECG gating. [30] The ultra-fast acquisition means that CM is required only for a short period of time, which allows the use of a low dose of CM. [31,32] Additional benefits include-lower radiation dose and reduced motion artifacts.…”
Section: High-pitch Helical Acquisitionmentioning
confidence: 99%